2023
DOI: 10.1002/adhm.202300167
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable CuMoO4 Nanodots with Multienzyme Activities for Multimodal Treatment of Tumor

Abstract: Due to their complexity and variability, tumors need to be treated with multimodal combined therapy, which requires the development of therapeutic agents that can provide multimodal therapeutic effects. Here, CuMoO4 nanodots smaller than 10 nm that can be prepared by simple hydrothermal method are reported. These nanodots can be well dispersed in water and have good biosafety and biodegradability. Further studies show that these nanodots also present multienzyme activities, such as catalase, peroxidase and glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The radiated tumor cell–released microparticles (RT‐MP) released by irradiated lung carcinoma cells can cause ferroptosis of tumor cells, and the release of extracellular CRT and ATP in the medium increased after treatment with RT‐MP [ 76 ]. Similarly, in recent studies investigating the use of nanomedicines to induce ferroptosis for cancer treatment, a few findings have highlighted the release of DAMPs by drug‐induced ferroptotic cancer cells [ 52 , 54 , 60 , 62 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], and in several studies, the promotion of DC maturation has also been reported [ 54 , 82 , 83 , 84 , 85 ]. In addition to the most well‐known DAMPs, namely HMGB1, ATP and CRT, Liu et al.…”
Section: The Crosstalk Between Ferroptosis and Anti‐tumor Immunity In...mentioning
confidence: 99%
See 1 more Smart Citation
“…The radiated tumor cell–released microparticles (RT‐MP) released by irradiated lung carcinoma cells can cause ferroptosis of tumor cells, and the release of extracellular CRT and ATP in the medium increased after treatment with RT‐MP [ 76 ]. Similarly, in recent studies investigating the use of nanomedicines to induce ferroptosis for cancer treatment, a few findings have highlighted the release of DAMPs by drug‐induced ferroptotic cancer cells [ 52 , 54 , 60 , 62 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], and in several studies, the promotion of DC maturation has also been reported [ 54 , 82 , 83 , 84 , 85 ]. In addition to the most well‐known DAMPs, namely HMGB1, ATP and CRT, Liu et al.…”
Section: The Crosstalk Between Ferroptosis and Anti‐tumor Immunity In...mentioning
confidence: 99%
“…Similarly, several studies have observed that ferroptotic breast cancer cells can release DAMPs [ 77 , 82 , 85 ], leading to the phenotypic maturation of DCs [ 82 , 85 ]. Furthermore, ferroptotic breast cancer cells enhance the infiltration of anti‐tumor immune cells [ 86 ], improve the immune microenvironment phenotype [ 56 , 58 , 85 , 118 , 121 ], and enhance the therapeutic efficacy of ICIs [ 56 ].…”
Section: The Interplay Between Ferroptosis and Anti‐tumor Immunity In...mentioning
confidence: 99%
“…In addition, the interactions between nanomaterials and biological components are not fully understood. 39 Therefore, the design and development of copper complexes, such as thiosemicarbazone copper complexes, for inducing cuproptosis in tumors show good promise. In addition, Cu(I) ions are more favorable for cuproptosis than Cu(II) because Cu(I) binds directly to lipoylated TCA cyclins, leading to greater toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The construction of nanoplatforms often requires complex operations. In addition, the interactions between nanomaterials and biological components are not fully understood . Therefore, the design and development of copper complexes, such as thiosemicarbazone copper complexes, for inducing cuproptosis in tumors show good promise.…”
Section: Introductionmentioning
confidence: 99%
“…Certain nanoparticles (NPs) show promise as anticancer agents by inducing cuproptosis. For instance, CuMoO4 nanodots may trigger cuproptosis in tumor cells, offering a promising approach for combined cancer therapy [ 150 , 207 ]. The HD/BER/GOx/Cu hydrogel system reduces dosing frequency and minimizes invasiveness in local cancer treatment, shrinking breast cancer size before surgery and suppressing tumor growth [ 208 ].…”
Section: Introductionmentioning
confidence: 99%